12. STUDY INTRA-ABDOMINAL HYPERTENSION IN PATIENTS WITH SEVERE ACUTE PANCREATITIS AT NGHE AN FRIENDSHIP GENERAL HOPITAL (Vietnam Journal of Community Medicine, 2023)
Backgroud: Increased intra-abdominal pressure is common in patients with acute pancreatitis, and increased intra-abdominal pressure occurs due to inflammatory processes in the pancreas, peritoneal fluid, paralytic ileus, and fluid resuscitation. Increased intra-abdominal pressure increases morbidity and mortality in patients with acute pancreatitis.Objectives: To evaluate the degree of increased intra-abdominal pressure in patients with acute pancreatitis and treatment prognosis according to the degree of increased intra-abdominal pressure. Subjects and methods: A case-series study of 31 patients diagnosed with acute pancreatitis according to Atlanta 2012 criteria at the Intensive Care Unit of Friendship Hospital in Nghe An from January 2020 to September 2020.Results: The mean age was 55.1 ± 20.5 years old, in which male: 77.4%. The rate of increased intraabdominal pressure was 61.3%. Classification according to the Balthazar classification of mild acute pancreatitis has 64.51% and 35.48% severe. According to Atlanta criteria, mild acute pancreatitis has 45.16 % and severe is 54.8%. Rate of increased intra-abdominal pressure grade I: 19.4, grade II: 22.5%; grade III: 12.9%, grade IV: 6.5%. Increased intra-abdominal pressure has a severe prognostic value according to the RANSON, IMRIE and APACHE II scales with an area under the curve of 0.86, respectively; 0.85 and 0.95. Failure of 1 organ, increased intra-abdominal pressure grade I, II. Failure of 3 organs, increased intra-abdominal pressure grade III, IV.Conclusion: The rate of increased intra-abdominal pressure was 61.3%. Increased intra-abdominal pressure has a classification value, predicts severity and is related to the number of organ failure in patients with acute pancreatitis.
Keywords: Acute pancreatitis, increased intra-abdominal pressure.